Reinforcement of Character Education Based on School Culture to Enhancing Elementary School Students' Citizenship Character - Lisa Retnasari; Yayuk Hidayah; Danang Prasetyo (Jurnal Ilmiah Sekolah Dasar, 2021)
The development of the nation's character has not shown progress in the progress of its citizens to become more characterized. The phenomenon is that many people's behavior is not by the character imbued with the Pancasila philosophy. This study aims to analyze the program for strengthening character education based on school culture as a strengthening of the civic character of elementary school students. The method used in this research is descriptive qualitative with data collection in interviews, observations, and documentation. The data analysis technique uses the Miles and Huberman method triangulation. The results showed that the school culture-based character education program is a civic reinforcement for students by familiarizing the main character values in religion, nationalism, independence, cooperation in various school cultural activities. In addition, there is support in the implementation of character education programs as an enhancer of entrepreneurial character in Ngrukeman Yogyakarta Elementary School students, such as adequate infrastructure and teacher training. This paper concludes that the school culture-based character education program as a strengthening of the civic character of students in elementary schools can be implemented with the cooperation of various parties in the school. The recommendations in this article are to explore further the school culture-based character education program, especially in elementary schools.